A Self-Management Programme of Activity Coping and Education - SPACE for COPD(C) - in primary care: The protocol for a pragmatic trial. Issue 7 (10th July 2017) - Bourne, Claire LA; Kanabar, Pratiksha; Mitchell, Katy; Schreder, Sally; Houchen-Wolloff, Linzy; Bankart, M John G; Apps, Lindsay; Hewitt, Stacey; Harvey-Dunstan, Theresa; Singh, Sally J
Abstract : Introduction: National guidance for chronic obstructive pulmonary disease (COPD) suggests that self-management support be provided for patients. Our institution has developed a standardised, manual-based, supported self-management programme: Self-Management Programme of Activity Coping and Education (SPACE for COPD(C)). SPACE was previously piloted on a 1-2-1 basis, delivered by researchers, to individuals with COPD. Discussions with stakeholders highlighted considerable interest in delivering the SPACE for COPD(C) intervention as a group-based self-management programme facilitated by healthcare professionals (HCPs) in primary care settings. The study aims are to explore the feasibility, acceptability and efficacy for the intervention to be delivered and supported by HCPs and to examine whether group-based delivery of SPACE for COPD(C), with sustained support, improves patient outcomes following the SPACE for COPD(C) intervention. Methods and analysis: A prospective, multi-site, single-blinded randomised controlled trial (RCT) will be conducted, with follow-up at 6 and 9 months. Participants will be randomly assigned to either the control group (usual care) or intervention group (a six-session, group-based SPACE for COPD(C)self-management programme delivered over 5 months). The primary outcome is change in COPD assessment test at 6 months. A discussion session will be conducted with HCPs who deliver the intervention to discuss and gain insight into any potential facilitators/barriers to implementing the intervention in practice. Furthermore, we will conduct semi-structured focus groups with intervention participants to understand feasibility and acceptability. All qualitative data will be analysed thematically. Ethics and dissemination: The project has received a favourable opinion from South Hampshire B Research Ethics Committee, REC reference: 14/SC/1169 and full R&D approval from the University Hospitals of Leicester NHS Trust: 152408. Study results will be disseminated through appropriate peer-reviewed journals, national and international respiratory/physiotherapy conferences, via the Collaboration and Leadership in Applied Health Research and Care and through social media. Trial registration: ISRCTN17942821; pre-results.